2017
DOI: 10.1051/0004-6361/201628705
|View full text |Cite
|
Sign up to set email alerts
|

Core-collapse supernova progenitor constraints using the spatial distributions of massive stars in local galaxies

Abstract: We study the spatial correlations between the H α emission and different types of massive stars in two local galaxies, the Large Magellanic Cloud (LMC) and Messier 33. We compare these to correlations derived for core-collapse supernovae (CCSNe) in the literature to connect CCSNe of different types with the initial masses of their progenitors and to test the validity of progenitor mass estimates which use the pixel statistics method. We obtain samples of evolved massive stars in both galaxies from catalogues w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 129 publications
2
23
0
Order By: Relevance
“…In comparison with other SN types it has also been shown that SNe IIn exhibit the least association with ongoing star formation compared to the other CCSNe (Habergham et al 2014). Kangas et al (2017) showed that the SN IIn population does not share a similar spatial distribution in host galaxy Hα light with LBV stars. They are instead best matched with the RSG stars, whose distribution suggests relatively lower mass compared to LBV stars.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison with other SN types it has also been shown that SNe IIn exhibit the least association with ongoing star formation compared to the other CCSNe (Habergham et al 2014). Kangas et al (2017) showed that the SN IIn population does not share a similar spatial distribution in host galaxy Hα light with LBV stars. They are instead best matched with the RSG stars, whose distribution suggests relatively lower mass compared to LBV stars.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence to show that SN type Ib originate from binary systems (Leloudas et al 2011;Eldridge et al 2013;Kuncarayakti et al 2013a;Folatelli et al 2016;Galbany et al 2016;Lyman et al 2016;Kangas et al 2017;Kuncarayakti et al 2018;Taddia et al 2018;Prentice et al 2019), whereby the SN progenitor loses its hydrogen envelope through mass transfer to its companion star rather than through stellar winds. It is also thought that at least some SNe Ic are the result of binary star interactions, although single star progenitor channels may also exist.…”
Section: Converting Stellar Age To Mmentioning
confidence: 99%
“…A key benefit of this analysis is that it provides a basic comparative measure of the location properties of different types of sources, such as SNe and the types of stars that are their likely progenitors (see e.g. Leloudas et al 2010;Kangas et al 2017); however, its main disadvantage is that it only probes the bulk properties of the environment, but not the specific physical processes associated with the evolution of populations of massive stars or their influence on the environments (Crowther 2013).…”
Section: Normalised Pixel Statisticsmentioning
confidence: 99%